2022
DOI: 10.18502/ijrm.v20i5.11054
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hsa-miR-30a-5p and nonobstructive azoospermia: A case-control study

Abstract: Background: Some previous human and animal studies have supported the idea that KDM3A down-regulation might be the main cause of male infertility, especially in nonobstructive azoospermia (NOA). The regulatory role of micro-RNAs (miRNA) has been investigated in the development of male infertility. Objective: The expression level of hsa-miR-30a-5p in azoospermia was evaluated to reveal its possible association with the etiology of male infertility. Materials and Methods: In this case-control study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Similarly, in olive flounder ( Paralichthys olivaceus ), miR-143, miR-26a and let-7a were also identified as the most expressed miRNAs in both ovaries and testes (Gu et al, 2014). In mouse and human, miR-30a-5p was crucial for spermatogonial stem cell differentiation (Khanehzad et al, 2021) and was used as a marker for men suffering from non-obstructive azoospermia (Arefnia et al, 2022). In our data, however, we observed a conserved overexpression of miR-30a in adult fish ovaries compared to adult testes in the ten studied species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in olive flounder ( Paralichthys olivaceus ), miR-143, miR-26a and let-7a were also identified as the most expressed miRNAs in both ovaries and testes (Gu et al, 2014). In mouse and human, miR-30a-5p was crucial for spermatogonial stem cell differentiation (Khanehzad et al, 2021) and was used as a marker for men suffering from non-obstructive azoospermia (Arefnia et al, 2022). In our data, however, we observed a conserved overexpression of miR-30a in adult fish ovaries compared to adult testes in the ten studied species.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the downstream genes TNP1, PRM1, and PRM2 remain silent. All of these factors combine to induce male infertility in men with NOA ( 39 ). MiR-126 can stimulate cell proliferation and restrain the apoptosis of immature porcine Sertoli cells by targeting the PIK3R2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was discovered that mir-122a can reduce TNP2 expression during spermatogenesis. Arefnia et al [ 27 ] demonstrated that the purpose of this miRNA is to inhibit gene expression by degrading the transcription of this gene.…”
Section: Discussionmentioning
confidence: 99%